Analisis Kajian Makna Simbolik dan Fungsinya dalam Pelestarian Pangan Padi pada Upacara Gren Mahe di Sikka Tana Ai - Yeremias Bardi; Robertus Adi Sarjono Owon; Desideratio Primus Naitili (Khatulistiwa: Jurnal Pendidikan dan Sosial Humaniora, 2026)
The Gren Mahe ceremony in Sikka Tana Ai is a traditional ritual that plays a crucial role in sustaining rice cultivation while representing the spiritual, social, and ecological relationships of agrarian communities. However, modernization and social change have posed challenges, leading to a decline in community participation and a shift in the symbolic meanings embedded within the ritual. This study aims to analyze the symbolic meanings and functions of the Gren Mahe ceremony in the context of local food preservation and to examine its relevance amid contemporary sociocultural dynamics. The research employs a symbolic ethnographic approach, consisting of three main stages: pre-research, field research, and post-research. Data collection techniques include participant observation, in-depth interviews with traditional elders, farmers, and community members, as well as documentation of the ritual. The data are analyzed using symbolic interpretation and triangulation methods to ensure validity. The findings are expected to contribute academically to cultural anthropology studies, provide strategic recommendations for food security policies based on local wisdom, and produce a scientific article published in a nationally accredited journal. Thus, this research reinforces the position of the Gren Mahe tradition as a cultural heritage that remains relevant for sustaining food security among the Sikka Tana Ai community.